Contextual factors in second language learning in a short-term study abroad programme in Australia. Issue 3 (27th May 2018) - Conroy, Mark Andrew
ABSTRACT: This study explored the experiences and language gains of Chinese-background English language learners living in homestays during a short-term study abroad (SA) programme in Australia. Forty-one learners took part in listening dictation pre- and post-tests to assess their acquisition of idiomatic phrasal verbs, and also completed weekly journals and diaries in which they reflected on their SA and homestay experiences. The journals and diaries were analysed to locate contextual factors which might explain individual learner's performances on the pre- and posts-tests. Most learners improved their ability to hear and transcribe the phrasal verbs, and the analysis of the journals and diaries identified several factors that appeared to contribute to the performance of the high and low achieving learners. The findings are discussed in terms of SA programmes and second language learning processes.